2014
DOI: 10.1002/bem.21865
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time assessment of possible electromagnetic‐field‐induced changes in protein conformation and thermal stability

Abstract: Previous studies on possible interactions of radiofrequency electromagnetic fields (RF EMFs) with proteins have suggested that RF EMFs might affect protein structure and folding kinetics. In this study, the isolated thermosensor protein GrpE of the Hsp70 chaperone system of Escherichia coli was exposed to EMFs of various frequencies and field strengths under strictly controlled conditions. Circular dichroism spectroscopy was used to monitor possible structural changes. Simultaneously, temperature was recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Slow freezing protocols combined with fast thawing rates and the use of cryoprotectants such as serum albumin are frequently used to improve LDH viability, but with moderate results [9]. Different authors have shown that the application of high-frequency electromagnetic fields at room temperature has non-thermal effects on macromolecules, proteins and enzymes [10][11][12][13][14] and, in particular, Vojisavljevic, Pirogova [11,15] showed that LDH activity could be modulated by electromagnetic waves in the microwave frequency range. However, to the best of our knowledge, no data exist on the effect of low-frequency OMFs on LDH activity.…”
Section: Introductionmentioning
confidence: 99%
“…Slow freezing protocols combined with fast thawing rates and the use of cryoprotectants such as serum albumin are frequently used to improve LDH viability, but with moderate results [9]. Different authors have shown that the application of high-frequency electromagnetic fields at room temperature has non-thermal effects on macromolecules, proteins and enzymes [10][11][12][13][14] and, in particular, Vojisavljevic, Pirogova [11,15] showed that LDH activity could be modulated by electromagnetic waves in the microwave frequency range. However, to the best of our knowledge, no data exist on the effect of low-frequency OMFs on LDH activity.…”
Section: Introductionmentioning
confidence: 99%